SERVICES AT THE WHITE WATER LAKE TOURIST ATTRACTION IN THE MERANTI ISLAND REGENCY - Nurhayati Nabila; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The White Water Lake Tourism Object in Teluk Samak Village is one of the lakes on Rangsang Island, Meranti Islands Regency, management at Tasik Air Putih is the local government and the surrounding community who work together to maintain and preserve the tourist attraction. Tasik Air Putih has been used for the Drinking Water Supply System (SPAM) in 5 villages in Rangsang District, a small portion of clean water has been circulated to 2500 residents' houses for the management of the drinking water supply system. Around Tasik Air Putih there is an island located in the middle of the lake, the existence of this island makes this lake look charming and has added value from other lakes, this area also has historical value for the local community. The purpose of this study was to analyze the services and constraints of the Tasik Air Putih Tourism Object in the Meranti Islands Regency. This study uses a qualitative method with a descriptive approach to describe the actual situation by collecting information data directly from the field. The key informants in this study were the Village Head, Village Apparatus, Community and Tourists. This study uses the technique of collecting observations, interviews and documentation. From the results of this study it can be seen that the services and constraints that exist in the Air Putih Lake Tourism Object Keywords : Services, Constraint, Object, Management